Health Status After Transcatheter or Surgical Aortic Valve Replacement in Patients With Severe Aortic Stenosis at Increased Surgical Risk: Results From the CoreValve US Pivotal Trial - Arnold, Suzanne V; Reynolds, Matthew R; Wang, Kaijun; Magnuson, Elizabeth A; Baron, Suzanne J; Chinnakondepalli, Khaja M; Reardon, Michael J; Tadros, Peter N; Zorn, George L; Maini, Brij; Mumtaz, Mubashir A; Brown, John M; et al. (JACC. Cardiovascular interventions, 2015)
This study sought to compare the health status outcomes for patients treated with either self-expanding transcatheter aortic valve replacement (TAVR) or surgical aortic valve replacement (AVR). In patients at increased surgical risk, TAVR with a self-expanding bioprosthesis is associated with improved 1-year survival compared with AVR. However, elderly patients may be just as concerned with quality-of-life improvement as with prolonged survival as a goal of treatment. Between 2011 and 2012, 795 patients with severe aortic stenosis at increased surgical risk were randomized to TAVR or AVR in the CoreValve US Pivotal Trial. Health status was assessed at baseline, 1 month, 6 months, and 1 year using the Kansas City Cardiomyopathy Questionnaire, Medical Outcomes Study Short-Form 12 Questionnaire, and EuroQOL 5-dimension questionnaire; growth curve models were used to examine changes over time. Over the 1-year follow-up period, disease-specific and generic health status improved substantially for both treatment groups. At 1 month, there was a significant interaction between the benefit of TAVR over AVR and access site. Among surviving patients eligible for iliofemoral (IF) access, there was a clinically relevant early benefit with TAVR across all disease-specific and generic health status measures. Among the non-IF cohort, however, most health status measures were similar for TAVR and AVR, although there was a trend toward early benefit with TAVR on the Short-Form 12 Questionnaire's physical health scale. There were no consistent differences in health status between TAVR and AVR at the later time points. Health status improved substantially in surviving patients with increased surgical risk who were treated with either self-expanding TAVR or AVR. TAVR via the IF route was associated with better early health status compared with AVR, but there was no early health status benefit with non-IF TAVR compared with AVR. (Safety and Efficacy Study of the Medtronic CoreValve® System in the Treatment of Symptomatic Severe Aortic Stenosis in High Risk and Very High Risk Subjects Who Need Aortic Valve Replacement; NCT01240902).